Notícias de um crime no mundo civilizado : as mortes de Galdino Pataxó - Souza, Ana Paula Freire de (2007)
The death of an indigenous leader in the capital city of Brazil. A crime committede by socially privileged adolescents. A diary newspaper directed to A and B classes whose profile is almost aways that of giving its assent to the public power o Globo. An insistent voice of a monthly tabloid that assumes the role of defending the indigenous causes, sponsored by the Catholic Church o Porantin. Through the heuristic method of Discourse Analyses, we try to understand how these different power structures make sense of the episode that was merely a practical joke to those who perpetrated it, being nevertheless fatal to the victim. Also, we intend to explain how both communication vehicles built the discursive web that ends up revealing the several deaths of Galdino Jesus dos Santos. Through DA, it is possible to read the language dialectically, understanding the discourse as the place where language and ideology meet.